COVID-19 mRNA or viral vector vaccine type and subject sex influence the SARS-CoV-2 T-cell response - Tong, Sherry; Litwin, Sean M.; Epel, Elissa S.; Lin, Jue; Drury, Stacy S.; Hecht, Frederick M.; Robinson, James E.; Prather, Aric A.; Norton, Elizabeth B. (Vaccine, 2025)
Severe SARS-CoV-2 infection has been partially controlled by vaccination, though issues in duration and breadth of protection remain. Few studies investigate factors driving diversity in the cellular immune response to vaccination. Here, we evaluated T-cell immunity in 60 healthy adults and its relationship to vaccine and subject-specific variables. CD4 and CD8 T-cells from COVID-19 vaccinated subjects expressed spike-specific activation-induced markers (AIM+) and cytokines. Overall, AIM+ CD8 T-cells correlated best with neutralizing antibodies and were more strongly expressed by females than males. Unique patterns in CD4 T-regulatory cells, cytokine profiles, and central and effector memory subsets were observed between Moderna, Pfizer, and Janssen vaccinees and by subject-specific factors. Sex differences outweighed differences in BMI and age. Thus, COVID-19 vaccine type and subject sex impacted the magnitude and quality of the spike-specific T-cell response. These results help explain differences in durability and memory between mRNA and adenovirus vector based COVID-19 vaccines and suggest targets for improved vaccine design.